Implementation of the Arts Center Approach in Increasing Early Childhood Creativity in Integrative Holistic Early Childhood Education - Rita Nofianti; Siti Latifah; Rabiatul Adawiyah (International Journal of Studies in International Education, 2025)
This study aims to describe the implementation of the art center approach in increasing early childhood creativity in Integrative Holistic Early Childhood Education. The art center approach is one of the child-centered learning strategies, by providing freedom of expression through art activities such as drawing, painting, dancing, and playing music. This study uses a qualitative method with a descriptive approach. The research subjects consist of teachers and children aged 4–6 years in Integrative Holistic Early Childhood Education. Data was collected through observation, interviews, and documentation, then analyzed with stages of data reduction, data presentation, and conclusion drawn. The results of the study show that the implementation of the art center approach in Integrative Holistic PAUD is able to foster aspects of children's creativity, including the ability to imagine, experiment with art media, and express ideas originally. In addition, the role of teachers as facilitators is very important in providing stimulation, a supportive environment, and appreciation of children's work. In conclusion, the art center approach is effective in developing early childhood creativity if applied consistently, with the support of facilities, media, and mentoring that are appropriate to the stage of child development.